Selected parameters of epidermal barrier in juveniles with type 1 diabetes correspond with the severity of diabetes – an observational study - Bogusz-Górna, Klaudia; Polańska, Adriana; Dańczak-Pazdrowska, Aleksandra; Żaba, Ryszard; Fichna, Piotr; Kędzia, Andrzej (Frontiers in Endocrinology, 2025)
BackgroundOur study aimed to evaluate the epidermal barrier function in children with type 1 diabetes. To the author’s knowledge, no studies have been conducted on epidermal barrier parameters, including TEWL and measurement of epidermal hydration, in children and adolescents with type 1 diabetes.MethodsOne hundred sixty children and adolescents aged 6-18, 125 patients with type 1 diabetes, and 35 healthy volunteers participated in the study: a detailed clinical evaluation, transepidermal water loss (TEWL) measurement, and epidermal hydration (corneometry) were carried out.ResultsPoor metabolic control in type 1 diabetes, higher HbA1c(%), and more frequent hyperglycemia impact TEWL and epidermis hydration. Also, the level of BF(%) correlated positively with TEWL.ConclusionsExtended supplementary tests – the assessment of TEWL and corneometry – could be included in the periodic examinations of children and adolescents with type 1 diabetes mellitus. Clinicians should always pay attention to dry skin in children with diabetes, and noninvasive examination (TEWL measurement and corneometry) may allow us to isolate a group at risk of neuropathy or the development of the diabetic foot. Further tests enabling detailed assessment of the usefulness of TEWL measurements and corneometry are needed.